Contractual liability for breach of the clauses of the negotiation contract - Mahrouk, Khaoula; BENISSAD, Adra (Journal of Human Sciences, 2025)
The negotiation contract is a preliminary contract that regulates the negotiation stage and imposes obligations on the negotiators, such as the principle of good faith. Violation of these obligations leads to contractual responsibility, and the defaulting negotiator is obligated to pay compensation if proven that the breach caused damage. However, it is permissible to modify its provisions within legal limits. The contractual responsibility is not specifically addressed, making it subject to general principles in civil law, which may not provide adequate legal protection for the negotiator who suffers from the breach of the other negotiator’s commitment, especially regarding the guarantee of obtaining compensation for damages.